PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI, DAN PELATIHAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN - Ariyanti, Tri (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2024)
The research conducted aims to see how much influence leadership style, communication and work training have on employee productivity. The population in this study were 91 employees at DISPERKIM Semarang City. The sample was determined using a saturated sample where all employees were respondents in the research. The results obtained were processed using the SPSS program and analyzed. The results of the analysis stated that all independent variables had a positive and significant influence on the anxiety variable with the highest significance value found in the communication variable of 0.306.